RED BLOOD CELLS OF THE SIAMESE JAMBAL (Pangasius hypophthalmus) FEED CONTAINING HYDROVAC VACCINE - Mardiana Siregar; Morina Riauwaty; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACKVaccines are weakened microorganisms aimed at raising the immunity of fish against a particular disease. The purpose of this research is to find out what is the best dosage of feed containing HydoVac vaccine on Siamese jambal siam fish (Pangasius hypophthalmus). This research has been conducted in April to August 2019 which is housed in the parasitic laboratory and fish disease Faculty of Fisheries and Marine of Riau University. The test fish used is the seed of a Siamese jambal siam fish that measures 8-10 cm by 150 tails.The method used in this research is a method of experimental with the complete random draft (RAL) a factor of 5 levels of treatment and 3 times repeated, the treatment is Kn (feeding without the Hydrovac vaccine and without test challenge with bacteria Aeromonas hydrophila), Kp (giving feed without HydroVac vaccine and test challenge with bacteria Aeromonas Hydrophila), P1 (addition of Hydrovac vaccine on feed at a dose of 6 ml/kg feed), P2 (the addition of Hydrovac vaccine in the feed at a dose of 8 ml/kg feed) and P3 (the addition of Hydrovac vaccine in the feed at a dose of 10 ml/kg feed). Fish maintained for 30 days in the aquarium, Test Challenge on the 31st day using the bacteria Aeromonas hydrophila. The measured parameters are total erythrocytes, hemoglobin concentration, hematocrit value, fatigue, relative percent survival (RPS), and absolute weight growth. Results showed that the addition of HydoVac vaccine on the feed can prevent the disease Motile Aeromonas Septicemia (MAS), judging from the total average eritosit 139x104 cells/mm3, hemoglobin 6,22 g/dL, Hematocrit value 25,11%, life 90%, relative percent survival (RPS) 85,18% and total weight growth 11.76 G. Based on the obtained data can be concluded that the addition of HydroVac vaccine in feed is able to increase the body resistance of the Siamese Jambal siam (Pangasius hypophthalmus).Keywords: Pangasius hyphophthalmus, vaccine HydroVac, Aeromonas hydrophila,